Kitab Suci Sumber Inspirasi Spiritualitas Tanggap Orang Muda Katolik - Siprianus Soleman Senda (BULLET : Jurnal Multidisiplin Ilmu, 2023)
The Holy Scriptures in the view of the Catholic Church are the Word of God in human language. The Word of God is a source of inspiration and guidance for human life with Catholic faith. Catholic Youth as the next generation of the future Church live in a pluralistic society. This presence should be an active presence in a responsive and involved social role for community development. So Catholic Youth explored the inspiration for responsive spirituality in the holy book. This research seeks to provide insight into the importance of the holy book as a source of inspiration for responsive spirituality for Catholic Youth. Through the method of involved observation and literature study, the problem of the lack of involvement of Catholic Youth in social roles is examined through a responsive spirituality that originates from the scriptures. The holy book is a source of inspiration for a responsive spirituality that moves Catholic Youth to be actively involved in social roles that empower the community.